Narrative theory : core concepts and critical debates - Herman, David, 1962-; Phelan, James, 1951-; Rabinowitz, Peter J., 1944-; Richardson, Brian, 1953-; Warhol, Robyn R. (Theory and interpretation of narrative series., 2012)
"Narrative Theory: Core Concepts and Critical Debates addresses two frequently asked questions about narrative studies: 'what is narrative theory?' and 'how do different approaches to narrative relate to each other?' In engaging with these questions, the book demonstrates the diversity and vitality of the field and promotes a broader dialogue about its assumptions, methods, and purposes. In Part One, the co-authors explore the scope and aims of narrative from four distinct perspectives: rhetorical (Phelan and Rabinowitz), feminist (Warhol), mind-oriented (Herman), and unnatural (Richardson). Using case studies (Huckleberry Finn, Persuasion, On Chesil Beach, and Midnight's Children, respectively), the co-authors explain their different takes on the same core concepts: authors, narrators, narration; plot, time, and progression; space, setting, and perspective; character; reception and the reader; and narrative values. In Part Two, the co-authors respond to one another's views. As they discuss the relation of the approaches to each other, they highlight significant current debates and map out key developments in the field."--